Studio Quiz Used as a Test to Comprehend Listening Skill: Perception of English Education Study Program Student of Tanjungpura University - Eusabinus Bunau (JETL (Journal of Education, Teaching and Learning), 2020)
This article is excerpted from research entitled Comprehending Listening Skill through Quiz. The quiz was administered to students of the English Education Study Program as a semester final test of Listening for Academic Purposes subject. The method of research is quantitative and intended to find out whether or not literature, sport, history, and general knowledge on the quiz was a matter for students to comprehend. The quiz administered to test the students was taken from www.bbclearningenglish.com. The primary data of the research was collected by surveying, and the secondary data was the result of the semester's final test. The survey was implemented by distributing a questionnaire to 43 student respondents attending the test. The technique of data analysis is descriptive. The research found that literature, sport, history, and general knowledge on the quiz were matters to students to comprehend. The matters were varied in accordance with skills characteristics such as the spelling of vocabulary, and the writing of phrase, sentence, and number.